Towards the minimal amount of exercise for improving metabolic health: beneficial effects of reduced-exertion high-intensity interval training - Richard Metcalfe (European Journal of Applied Physiology, 2012)
High-intensity interval training (HIT) has been proposed as a time-efficient alternative to traditional cardiorespiratory exercise training, but is very fatiguing. In this study, we investigated the effects of a reduced-exertion HIT (REHIT) exercise intervention on insulin sensitivity and aerobic capacity. Twenty-nine healthy but sedentary young men and women were randomly assigned to the REHIT intervention (men, n = 7; women, n = 8) or a control group (men, n = 6; women, n = 8). Subjects assigned to the control groups maintained their normal sedentary lifestyle, whilst subjects in the training groups completed three exercise sessions per week for 6 weeks. The 10-min exercise sessions consisted of low-intensity cycling (60 W) and one (first session) or two (all other sessions) brief ‘all-out’ sprints (10 s in week 1, 15 s in weeks 2–3 and 20 s in the final 3 weeks). Aerobic capacity ( V˙O2peakV˙O2peak ) and the glucose and insulin response to a 75-g glucose load (OGTT) were determined before and 3 days after the exercise program. Despite relatively low ratings of perceived exertion (RPE 13 ± 1), insulin sensitivity significantly increased by 28% in the male training group following the REHIT intervention (P < 0.05). V˙O2peakV˙O2peak increased in the male training (+15%) and female training (+12%) groups (P < 0.01). In conclusion we show that a novel, feasible exercise intervention can improve metabolic health and aerobic capacity. REHIT may offer a genuinely time-efficient alternative to HIT and conventional cardiorespiratory exercise training for improving risk factors of T2D.